2019
DOI: 10.2147/ott.s221219
|View full text |Cite
|
Sign up to set email alerts
|

<p>EFEMP2 Inhibits Breast Cancer Invasion And Metastasis In Vitro And In Vivo</p>

Abstract: BackgroundEGF-containing fibulin-like extracellular matrix protein 2 (EFEMP2) is an extracellular matrix (ECM) glycoprotein, which is regarded as potential prognostic biomarkers in some carcinoma. Little is known about the association of EFEMP2 and breast cancer.MethodsEFEMP2 expressions in normal breast tissue, benign fibroadenoma, breast cancer, the normal mammary epithelial cell line, and 4 different invasive breast cancer cell lines were evaluated by immunohistochemistry (IHC) or immunocytochemistry (ICC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Another report showed that DDR2 mediates stromal and cancer cell interaction in mesenchymal stem cells and metastasis growth in breast cancer (17,18). EFEMP2 significantly inhibits the invasion and metastasis of tumor cells and the process of epithelial-mesenchymal transition (EMT) through the Wnt/bcatenin pathway in lung, bladder, and breast cancers (19)(20)(21). Similarly, ITGBL1 is involved in tumor cell invasion and metastasis through the KRAS/EMT pathway (22).…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed that DDR2 mediates stromal and cancer cell interaction in mesenchymal stem cells and metastasis growth in breast cancer (17,18). EFEMP2 significantly inhibits the invasion and metastasis of tumor cells and the process of epithelial-mesenchymal transition (EMT) through the Wnt/bcatenin pathway in lung, bladder, and breast cancers (19)(20)(21). Similarly, ITGBL1 is involved in tumor cell invasion and metastasis through the KRAS/EMT pathway (22).…”
Section: Discussionmentioning
confidence: 99%
“…reported that EFEMP2 increases the invasive ability of cervical cancer cells by promoting EMT via the Raf/MEK/ERK signaling pathway. In contrast, Kang et al 29 . reported that EFEMP2 inhibited breast cancer invasion and metastasis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 90%
“…Early studies have shown that EFEMP2 is a product of a candidate oncogene, in mutant p53-independent or dependent mutants, it can exhibit its oncogenic activity [7]. In recent years, the expression of EFEMP2 in different types of cancers has been controversial, in that, in cancers, such as breast, lung, and endometrial cancers, EFEMP2 plays a protective role [8][9][10][11][12]. On the contrary, in cancers, such as ovarian cancer, glioma, osteosarcoma, and aneurysm, EFEMP2 is highly expressed, considered a candidate oncogene, and associated with poor prognosis of the tumors [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%